Category labels can influence the effects of selective retrieval on nonretrieved items. - Wirth, Michael; Bäuml, Karl-Heinz T. (Memory & Cognition, 2020)
Using lists of unrelated items as study material, recent studies have shown that selective retrieval of some studied items can impair or improve recall of the nonretrieved items, depending on whether the lag between study and selective retrieval is short or long. This study examined whether the results generalize when the items are studied together with their category labels (e.g., bird-magpie) and the category labels are reexposed as retrieval cues at test (e.g., bird-m___), a procedure often used in research on the effects of selective retrieval. Two lag conditions were employed in this study: a short 1-min lag between study and selective retrieval, and a longer 15-min lag that included mental context change tasks to enhance the lag-induced contextual drift. Experiment 1 employed lists of unrelated items in the absence of any category labels and replicated both the detrimental effect (after short lag) and the beneficial effect (after long lag) of selective retrieval. Experiment 1 was identical to Experiment 1 but provided the items' category labels during both study and retrieval, and Experiment 1 was identical to Experiment 1 but employed a categorized list. In both experiments, selective retrieval impaired recall in both lag conditions, indicating a critical role of category labels for the effects of selective retrieval. The results of the three experiments are consistent with a two-factor explanation of selective retrieval and the proposal that reexposure of category labels during retrieval can reinstate study context after longer lag.